Historical journey of wrestling from ancient Egypt to today - Akinci, A. Y. (International Journal of Applied Exercise Physiology, 2020)
The journey of wrestling which began approximately 5,000 years ago in a Sumerian temple, continued with a wrestling handbook in an Egyptian wall painting dating from 1850 BC. Later became one of the Ancient Olympic sports event, then completed the ancient journey as Greek type games in Rome. The abundance of resources from the Greek and Roman periods is perhaps due to the fact that Greek sports are pioneers around the Mediterranean. The literary and physical cultural elements are full of evidence that shows the prevalence and application of wrestling from Sumer to the present. The aim of this study is to examine the wrestling that took place in Egypt hundreds of years before Ancient Greece. In ancient Egypt, sports have been closely linked to religion, like all other aspects of culture. Ancienticonographic and literary evidence has been used to explain the popularity of wrestling in Egyptian Civilization in light of ethnographic studies. While creating the theoretical framework, various epigraphic records and source works in the field have beenused, information about the past practices of wrestling has been obtained, and the related resources have been scanned and images have been reached. Based on the data obtained, inferences have been made for the purposes of the research. It was concluded that the technical and tactical practices applied in ancient Egyptian wrestling are partially applied in today's wrestling, the referee management continues, but the subject of clothing is different due to the globalization of regional cultural values.